تقييم فعالية شبكة التيتانيوم في تدبير كسور قاع الحجاج - خليل, عبد الكريم; سليمان, يوسف; آغا, عبد السلام علي (Latakia University Journal -Medical Sciences Series, 2016)
هدفت هذه الدراسة إلى تقييم فعالية شبكة التيتانيوم في إصلاح كسور قاعدة الحجاج المعزولة أحادية الجانب . تألفت عينة البحث من 15حالة راجعت قسمي العينية و جراحة الفم و الفكين في مشفى الأسد الجامعي، مع كسور قاعدة حجاح معزولة أحادية الجانب وتم أخذ عامل الزمن لإجراء الجراحة بعد الرض بعين الاعتبار . تضمنت المراقبة السريرية دراسة حركات العين و التوضع العمودي لكرة العين وازدواجية الرؤيا خلال 15يوما وشهر وثلاثة أشهر بعد العمل الجراحي. وتمت متابعة الخوص خلال ثلاثة أشهر وستة أشهر بعد الجراحة . أظهرت النتائج وجود فروق ذات دلالة إحصائية خلال فترة المتابعة بعد للعمل الجراحي حيث عادت حركات العين بشكل كامل بعد ثلاثة أشهر وكذلك عاد التموضع الطبيعي لكرة العين للناحية المصابة مقارنة بكرة العين للجهة السليمة وكذلك تراجع الشفع خلال فترة المتابعة . أدى استخدام شبكة التيتانيوم في إصلاح كسور قاع الحجاح إلى تحسين الناحية الوظيفية لكرة العين وعودة الناحية الوظيفية والجمالية لهذا الجزء الهام من الوجه .The aim of this study to assesment the effect of using titanium mesh to repair isolated monolateral blow- out orbital fractures. The research sample comprised 15cases reported to the Department of ophthalmology and department of oral and maxillofacial surgery at Alassad University Hospital Latakia-Syria , the time between trauma and procedure of surgery was taken into account. The clinical observation contained studying of eye movement , vertical localization of eyeball, diplopia through15 day, month, and 3month after the surgery . The enophthalmos was monitored also through: 3 months ans 6 months after the surgery Results showed that there is statistical difference before and after the surgery operation. Eye movement returned completely normal after 3 months, the localization of injured side of eyeball returned natural when compared to the localization of intact side, and diplopia was corrected through the catamnesis Using Titanium mesh in repairing blow- out fractures led to improve the functional side of eyeball, so this important part of face was returned functionally and esthetically.